Analisis Pengaruh Net Interest Margin Dan Non Interest Income Terhadap Return On Asset Pada Badan Usaha Perbankan Di Bursa Efek Indonesia - Anita Permatasari (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2014)
The primary objective of this study is to determine which dominant factor to influence the profitability of banks in Indonesia. There are the two main factors that affect the profitability of the banks. The first one is Net Interest Margin as lo known as NIM and the second one is Non Interest Income also known as NII. Firstly, bank is in charge of collecting funds from the people and to channel it back to the community for various purposes. By doing this, Net Interest Margins are generated by the difference between saving rate and credit rate. Secondly, bank gains Non Interest Income by charging fee for banking services such as transfer fee, letter of credit, safe deposit box rental, etc. With higher Net Interest Margin and Non Interest Income, banks will achieve higher profitability. This research concludes that Net Interest Margin dominates over Non Interest Income in Indonesian’s banking. This research also concludes that Net Interest Margin and Non Interest Income can complement each other to increase banking sector profitability.